Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s00266-004-4031-4
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Middle Vault Support: A New Technique

Abstract: A novel technique for maintaining internal nasal valve anatomic and physiologic integrity at the time of hump reduction is proposed. The procedure involves mobilizing the anterior edge of the upper lateral cartilage after submucosal dissection. Reduction of the anterior border of the septal cartilage and reconstruction of the middle vault of the nose is accomplished by placing the upper lateral cartilage medial border on the reduced edge of the septum using a vest-over technique. The technique was successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Currently, reconstitution of the dorsum can involve narrowing the defect with osteotomies, insertion of spreader grafts, or turning over of the upper lateral crura as spreader flaps. [10][11][12][13][14][15][16][17] The natural fusiform dorsal lines of the nasal dorsum are created anatomically by the spread of the cartilaginous vault and its overlying cap of bony dorsum, with the widest point at the keystone area ( Figure 2). In addition, the dorsal septum is 1 to 2 mm below the ULC in the keystone area.…”
Section: Dorsal Modification-the Libra Graftmentioning
confidence: 99%
“…Currently, reconstitution of the dorsum can involve narrowing the defect with osteotomies, insertion of spreader grafts, or turning over of the upper lateral crura as spreader flaps. [10][11][12][13][14][15][16][17] The natural fusiform dorsal lines of the nasal dorsum are created anatomically by the spread of the cartilaginous vault and its overlying cap of bony dorsum, with the widest point at the keystone area ( Figure 2). In addition, the dorsal septum is 1 to 2 mm below the ULC in the keystone area.…”
Section: Dorsal Modification-the Libra Graftmentioning
confidence: 99%
“…Therefore, when performing a rhinoplasty, the surgeon must have thorough knowledge of the three nasal vaults and the dynamic interplay between them [1][2][3].…”
mentioning
confidence: 99%
“…In many previous studies, improvement in nasal air flow has been evaluated based on patient feedback. However, those studies did not analyze the feedback statistically (Seyhan, 1997;Acarturk and Gencel, 2003;Fayman and Potgieter, 2004;Byrd et al, 2007;Gruber et al, 2007;Neu, 2009;Manavbaş ı and Baş aran, 2013). In our present study, rhinomanometric analysis showed that the NAR significantly decreased in the postoperative period.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous suture techniques have been described to eliminate drawbacks (Seyhan, 1997;Acarturk and Gencel, 2003;Fayman and Potgieter, 2004;Byrd et al, 2007;Gruber et al, 2007;Neu, 2009;Manavbaş ı and Baş aran, 2013). These techniques are based on folding the ULC with mattress sutures, since the ULC is approximately four times thinner than spreader grafts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation